Circular RNA circ-Olfm1 induces progression of Alzheimer’s disease by regulating FOXO3a - YANG Hongyan; LIAO Qirong; HOU Mingliang (陆军军医大学学报)
Objective‍　‍To investigate the role of circular RNAs （circRNA） in Alzheimer’s disease （AD） and its potential mechanism. Methods‍　‍Six-month-old APP/PS1 mouse model of AD and wild type (WT) mice were subjected and then randomly divided into WT group, WT+ circ-Olfm1 knockout group, AD group (transgenic APP/PS1 mice), AD+ circ-Olfm1 knockout group, AD+FOXO3a knockout group, with 3 mice in each group. ① The total RNA of mouse brain was extracted, and the differential expression of circRNAs and mRNAs between the AD mice and WT mice was detected, and the obtained circRNAs and mRNAs were analyzed with gene ontology (GO) analysis. ② RT‐qPCR was used to detect the expression of the top 10 up-regulated and down-regulated circRNAs, as well as the expression of circ-Olfm1 and miR-330-5p. ③ Lentiviral vectors were prepared and stereotaxically injected into the cortex or hippocampus of WT and AD mice to knock out circ-Olfm1 gene. Water maze test was used to evaluate the effect of circ-Olfm1 knockout on cognitive function, and immunofluorescence assay was employed to observe the deposition of amyloid β (Aβ) plaque in the brain. ④ The interaction between circ-Olfm1 and miR-330-5p was verified by double luciferase reporter gene analysis. ⑤ The protein levels of AMPK and FOXO3a were detected by Western blotting. ⑥ Transmission electron microscopy was utilized to observe the mitochondria of the hippocampus. ⑦ The levels of inflammatory factors IL-6, IL-1β and TNF-α were detected by ELISA. Results‍　‍There were totally 52 differentially expressed circRNAs identified between the AD and WT mice, including 28 up-regulated and 24 down-regulated (fold change >1.5, P<0.05). These differentially expressed genes are mainly involved in signal transduction, learning and memory and other functions. circ-Olfm1 was identified as the most significantly differentially expressed circRNA, which is highly expressed in the neurons and up-regulated in the cerebral cortex and hippocampus of the AD mice. Knockout of circ-Olfm1 reduced the number of Aβ plaques in the cerebral cortex and hippocampus of AD mice (P<0.01). In starBase database, there are complementary sequences observed between circ-Olfm1 and miR-330-5p. Western blotting showed that the addition of Aβ42 significantly increased the expression of AMPK and FOXO3a in the neuronal cells (P<0.01). And silencing circ-Olfm1 led to decreased expression of AMPK and FOXO3a in neuronal cells+Aβ42 (P<0.01). ELISA revealed that knockout of FOXO3a significantly increased the levels of inflammatory factors IL-6, IL-1β, and TNF-α (P<0.01). Transmission electron microscopy displayed that knocking FOXO3a out significantly aggravated mitochondrial damage (P<0.01). Conclusion‍　‍circ-Olfm1 is up-regulated in the brain tissue and neurons+Aβ42 of AD rats, and the mechanism of cognitive impairment in AD rats may be through its regulating FOXO3a protein.